(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To preliminarily evaluate the feasibility of pelvic floor ultrasound in assessing stress urinary incontinence (SUI) in women, in comparison with dynamic pelvic floor magnetic resonance imaging (MRI). Methods: A cross-sectional study was conducted on 8 female patients diagnosed with SUI. Morphological and dynamic pelvic floor parameters were measured using ultrasound and compared with dynamic MRI findings. Correlations between the two modalities were assessed using Pearson’s correlation coefficient. Results: The mean age was 56.6 ± 9.5 years, with a mean parity of 3.6 ± 2.2. Most patients were classified as Stamey grade I–II. The posterior urethrovesical angle (PUVA) increased during Valsalva and showed good correlation between ultrasound and MRI (r = 0.79). Levator hiatus area demonstrated very high correlation (r = 0.97 during Valsalva). Bladder descent also showed strong correlation (r = 0.83), whereas bladder neck mobility showed weak correlation (r ≈ 0.17). Bladder neck funneling was observed in 25% of cases, with complete agreement between dynamic MRI and pelvic floor ultrasound. Conclusion: Preliminary findings suggest that pelvic floor ultrasound can reflect morphological and dynamic changes of the pelvic floor with a certain degree of correlation to MRI. Ultrasound may serve as a useful initial assessment tool; however, larger studies are required to validate these findings.